Extensional episodes in the Paleoproterozoic Capricorn Orogen, Western Australia, revealed by petrogenesis and geochronology of mafic–ultramafic rocks - Olierook, Hugo; Sheppard, Steve; Johnson, S.; Occhipinti, S.; Reddy, Steven; Clark, Christopher; Fletcher, I.; Rasmussen, B.; Zi, Jianwei; Pirajno, F.; LaFlamme, C.; Do, T.; et al. (Elsevier BV, 2018)
© 2017 Extensional episodes in Precambrian orogens are often difficult to decipher because of subsequent orogenesis and intracontinental reworking. Here, we use geochemical and geochronological constraints of a suite of preserved mafic–ultramafic rocks in the Paleoproterozoic Capricorn Orogen of Western Australia to reveal ophiolites, continental ribbons and aborted rifts. The Capricorn Orogen separates the Archean Yilgarn and Pilbara cratons and includes mafic–ultramafic rocks of the fault-bounded Trillbar Complex and Bryah Sub-basin. The Trillbar Complex is situated within a fault wedge between the Yilgarn Craton and a reworked portion of the craton to the north (Yarlarweelor Gneiss Complex), and has been variously interpreted as an obducted ophiolite, oceanic plateau or continental rift-related magmatic suite. In this study, a new U–Pb zircon age of 2069 ± 9 Ma from the Trillbar Complex indicates that it is at least 40 Myr older than the mafic and ultramafic rocks of the Bryah Sub-basin, with which it has previously been linked. The Trillbar Complex is characterised by E-MORB-like signatures, hydrous crystallization and a lack of crustal contamination, and probably formed in a mid-ocean ridge or, alternatively, an oceanic intraplate setting. Conversely, the 2030–1990 Ma mafic and ultramafic rocks in the Bryah Sub-basin show evidence of crustal contamination and are interpreted to have formed in a continental rift setting. Moreover, there is no evidence for boninites in the Bryah Sub-basin and, therefore, no justification for invoking a fore-arc setting. Thus, these pieces of evidence reveal a different tectonic and geodynamic origin for the Trillbar Complex compared to the Bryah Sub-basin rocks. The tectonic setting for the Trillbar Complex requires oceanic crust to have existed between the Yilgarn Craton and the Yarlarweelor Gneiss Complex. However, almost identical Archean histories of these crustal blocks support a proximal origin for the Yarlarweelor Gneiss Complex and a likely origin as a microcontinental ribbon. Farther east (in present-day coordinates), the Bryah Sub-basin and other sedimentary basins record punctuated rifting that never led to the formation of oceanic crust. Therefore, rigorous evaluation of high quality geochemical data coupled to geochronology from mafic–ultramafic rocks is able to provide valuable constraints on extensional episodes, where other evidence has since been erased from the rock record.